Jean-Jacques et Hippolyte, deux commandeurs meneurs de grève, ou comment sonner l’alarme à la sucrerie des Manquets (Saint-Domingue, 1782) - Jean-Louis Donnadieu (Transatlantica)
Studying family papers and plantation estates may be useful to discover new items about the former pro-slavery colonial society in the Americas. For instance, in 1782 on the Manquets sugar estate (in l’Acul, northern Saint-Domingue), a slaves’ strike led by two drivers, Jean-Jacques and Hippolyte, occured. Letters from the overseer Bayon de Libertat to the count of Noé, the absentee owner, narrate the events in the writer’s own interests, through vague explanations and criticism towards both leaders. The analysis of these letters, however, completed with the examination of other documents from other sources, shows that the overseer’s responsibility was far from being insignificant and that his way of running the estate, from 1779 to 1789, was very approximate, leading to an explosive situation. This didn’t escape the notice of the leaders of the August 1791 forthcoming slaves’ riot.